Analysis of acoustic field characteristics of mesoscale eddies throughout their complete life cycle - Ma, Xiaodong; Zhang, Lei; Xu, Weishuai; Li, Maolin (Frontiers in Marine Science, 2025)
Mesoscale eddies exert a profound influence on oceanic temperature and salinity structures, thereby altering the ecological environment and acoustic propagation characteristics. Prior research on acoustic propagation beneath mesoscale eddy effects has predominantly concentrated on fragmented, snapshot-style analyses. In contrast, this study employs a holistic approach by integrating multi-source data to elucidate oceanic temperature and salinity structures, ultimately impacting their ecological environment and acoustic propagation. While the existing paper, this study adopts a more comprehensive and successional methodology. Through the amalgamation of multi-source data, this research introduces an innovative mesoscale eddy tracking algorithm and an enhanced Gaussian eddy model. Utilizing the BELLHOP ray theory model, this investigation scrutinizes the acoustic field characteristics of a cyclonic eddy and a typical anticyclonic eddy (CE-AE) pair exhibiting complete life cycles in the Northwest Pacific. The results reveal that the complete life cycles of mesoscale eddies substantially impact the acoustic field environment. As a CE intensifies, the convergence zone (CZ) distance diminishes, the CZ width expands, and the direct wave (DW) distance shortens. Conversely, an intensifying AE increases the CZ distance, contracts the CZ width, and prolongs the DW distance. This paper presents a quantitative analysis to delineate the critical factors influencing eddy life cycles, indicating that both eddy intensity and deformation parameters significantly affect acoustic propagation characteristics, with eddy intensity exerting a more substantial influence. This research substantially contributes to the application of sea surface altimetry data for underwater acoustic studies and provides preliminary insights into the impacts of eddy parameters on underwater acoustic propagation within typical mesoscale eddy environments. Moreover, this research offers a foundation for future investigations into the intricate relationships between eddy dynamics and acoustic propagation in oceanic systems.